Kata Adalah Senjata: Sastra dan Perlawanan Zapatista dalam Menghadapi Pemerintah Meksiko - Nugraha, Dediyan Adnan (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
ABSTRACT This research aims to conduct an in-depth study of Zapatista literature and resistance in dealing with the neoliberal Mexican government. In general, this research wants to answer the question of "how does literature become a tool of Zapatista resistance in dealing with the Mexican government?". To test the problem, researchers conducted research using a historical method that included four research steps. The research steps include collecting written sources through literature study (heuristics), source criticism, source interpretation or analysis and historiography. Researchers also use concepts to simplify analysis, including the concept of social movements and literary theory. In its implementation, the Zapatista movement becomes a movement that uses literature as an expression of a movement that is non-violent or does not require physical fighting. Besides the Zapatista movement still has weapons for possible physical war with the Mexican government. Literature became a weapon for the Zapatistas, through his communication Marcos convinced it all.